Otimização do cultivo de Bacillus megaterium recombinante em bateladas alimentadas - Suárez, Carlos Alberto Galeano (2010)
Penicillin Acylases are enzymes of great industrial importance, being used mainly for production of 6-aminopenicillanic acid, 6-APA from penicillin G. In the late 90's, its use for synthesis of β-lactam semisynthetic antibiotics began on an industrial scale, an alternative in the context of "green chemistry" to the chemical synthesis of high environmental impact. The aiming thesis was to evaluate the influence of the growth media on the strains of Bacillus megaterium that will be used in the cloning of the gene pac in own B. megaterium, aiming at a larger number of copies of the gene, thus increasing the levels of expression of the enzyme penicillin G Acylase (PGA). It was determined the main metabolites produced by strains ATCC 14945 QB 1551 and PV 361 (the latter given by Professor Patricia Vary, corresponding to the wild QB 1551 with all megaplasmids deleted, which will be cloned with enzyme PGA). Evaluated medium has some influence on the metabolism of the organism, in order to optimize the production of the enzyme in cultures of high cell concentrations. The analysis of experimental data showed the strain PV 361 reached the highest cell concentration 16,6 g / L (dry weight), in fed-batch cultivation with the SNB medium with cheese whey (10,0 g / L), compared with 12,5 g / L without the presence of whey and 9,6 g / L in the LB-B medium. In cultures in SNB medium with whey the concentration of lactic acid reached 22,1 g/L, compared with 13,2 g/L in the absence of whey. However for the LB-B medium, the main product was acetic acid with a concentration of 6,7 g /L. Kinetic parameters were calculated as μmax, Yx/s, during the fed-batch cultivations in a bioreactor in stirred tank and aerated in a bench scale (5 L and 2L). The kinetic model for growth and production of metabolites was defined from the test phase in bioreactor batch. The operation of fed-batch culture and pH control were not effective for improving the production of biomass, because it had a high lactic acid production (up to 8 g / L in phase with the batch means SNB) and acetic acid (above 6 g / L at the end of the batch with LB medium-B), concentrations that led to the inhibition of growth of the microorganism and induced its sporulation, biological phenomenon that once started is difficult to reverse and that hinders the production in high cell density (HCDC).